Current views on the pharmacological correction of iron deficiency conditions in gynecological practice - Aleksandr S. Dukhanin (IP Berlin A.V., 2021)
The review considers features of iron and folic acid (FA) pharmacokinetics, which affect the effective micronutrient support: molecular mechanisms of absorption and distribution, homeostatic processes of maintaining plasma vitamin and mineral levels by the feedback mechanism, including by regulating the deposition. An important characteristic of ferrokinetics is the presence of unique iron exporter ferroportin which is controlled by a family of iron regulatory proteins. Systemic ferrotherapy and oral rout of iron delivery are distinguished. In general, parenteral iron preparation complexes consist of Fe(III) oxide/hydroxide core stabilized by a carbohydrate polymer shell. Once entering the bloodstream, iron complexes are absorbed by resident macrophages of the reticuloendothelial system of the liver, spleen and bone marrow. Systemic Fe(III) preparations are prodrugs, the active part of which, i.e. iron is released in the lysosomal matrix of phagocytes. Oral iron preparations are divided into those containing bivalent (ferrous) and trivalent (ferric) iron. The article discusses factors determining the differences in the absorption of oral ferrous and ferric iron preparation, the spectrum of side effects, as well as key pharmaceutical approaches to increase the tolerance and adherence of ferrotherapy. These include using preparations containing Fe(II) organic compounds that have a lower dissociation rate than inorganic iron salts as well as slowing down the release of the active Fe(II) pharmaceutical substance from the drug. The review pays special attention to folates as iron synergists and examines the features of FA pharmacokinetics, the molecular basis of synergism, and substantiates the use of combined iron and FA preparations.